Early Carboniferous extension in East Avalonia: 350 My record of lithospheric memory. (April 2018) - Smit, Jeroen; van Wees, Jan-Diederik; Cloetingh, Sierd
Abstract: Despite reactivations during Variscan and Alpine orogenies and the opening of the Northern Atlantic, Avalonia is one of the few regions where the initial Mid-Paleozoic basin structure is still recognisable, largely intact, and well studied. Its kinematics and dynamics remain, however, largely unknown, in particular in view of the successive late Paleozoic to recent evolution of the basin. Consequently, the importance of the mid-Palaeozoic tectonic evolution and structural controls are often overlooked and poorly understood in basin studies. In this paper, we reassess the importance of Mid-Palaeozoic tectonics on subsequent sedimentary basin evolution of north-western Europe. To this end, we analyse the dynamics of early Variscan extension in Avalonia based on the integration and re-evaluation of available geophysical and geological data from lithosphere to basin scales. Based on a revised crustal map of the Thor suture zone, we present a new paleo-tectonic reconstruction and tectonic scenario for the Devonian-Carboniferous rifting. These findings are key for a better understanding of long-lived tectonic segmentation and post-rifting deformation phases. Our findings indicate that the structural grain of many crustal fault dominated sedimentary basin structures such as the North Sea Central Graben were created in the early Carboniferous. Consequently, the main basement structuration of northwest Europe was completed before the Variscan orogeny and successive post-Variscan extension and inversion phases reactivated the existing basement structures without creating major new fault groups. Incorporation of the Paleozoic structural grain allows for a consistent tectonic framework for the Mesozoic, contributing to fundamental understanding of basin evolution. From our tectonic framework analysis, Avalonia therefore stands out as a fine example of long lived lithosphere memory, spanning over 350 My of structural control in geodynamic evolution. Highlights: Revised map of the tectonic setting of East Avalonia, its crustal units and extend in the lower crust and upper mantle. A new paleo-tectonic reconstruction and tectonic scenario for the Devonian-Carboniferous rifting of Avalonia. Map view restoration suggests back-arc extension by slab rollback along Avalonia's active Rheic margin. Slab rollback implies a northward subducting slab under Avalonia's active Rheic margin in the lower Carboniferous. The main basement structuration of northwest Europe was completed before the Variscan orogeny. Successive post-Variscan tectonic phases reactivated existing basement structures without creating major new fault groups.